Factors Predicting the Presence of Maternal Cells in Cord Blood and Associated Changes in Immune Cell Composition - Haddad, Marina El; Karlmark, Karlin R.; Donato, Xavier-Côme; Martin, Gabriel V.; Bretelle, Florence; Lesavre, Nathalie; Cocallemen, Jean-François; Martin, Marielle; Picard, Christophe; Roudier, Jean; Desbriere, Raoul; Lambert, Nathalie C. (Frontiers in Immunology, 2021)
Background: Cord blood (CB) samples are increasingly used as a source of hematopoietic stem cells in transplantation settings. Maternal cells have been detected in CB samples and their presence is associated with a better graft outcome. However, we still do not know what influences the presence of maternal microchimerism (MMc) in CB samples and whether their presence influences CB hematopoietic cell composition. Patients and methods: Here we test whether genetic, biological, anthropometric and/or obstetrical parameters influence the frequency and/or quantity of maternal Mc in CB samples from 55 healthy primigravid women. Mc was evaluated by targeting non-shared, non-inherited Human Leukocyte Antigen (HLA)-specific real-time quantitative PCR in whole blood and four cell subsets (T, B lymphocytes, granulocytes and/or hematopoietic progenitor cells). Furthermore CB samples were analyzed for their cell composition by flow cytometry and categorized according to their microchimeric status. Results: MMc was present in 55% of CB samples in at least one cell subset or whole blood, with levels reaching up to 0.3% of hematopoietic progenitor cells. Two factors were predictive of the presence of MMc in CB samples: high concentrations of maternal serological Pregnancy-Associated-Protein-A at first trimester of pregnancy (p=0.018) and feto-maternal HLA-A and/or –DR compatibility (p=0.009 and p=0.01 respectively). Finally, CB samples positive for MMc were significantly enriched in CD56+ cells compared to CB negative for MMc. Conclusions: We have identified two factors, measurable at early pregnancy, predicting the presence of maternal cells in CB samples at delivery. We have shown that MMc in CB samples could have an influence on the hematopoietic composition of fetal cells. CD56 is the phenotypic marker of natural killer cells (NK) and NK cells are known to be the main effector for graft versus leukemia reactions early after hematopoietic stem cell transplantation. These results emphasize the importance of MMc investigation for CB banking strategies.